A Mathematical Algorithm Approach for Estimating Water-Based Paint Requirements for a Given Wall - Gambi, Costance P.; Taifa, Ismail W.R. (Tanzania Journal of Engineering and Technology, 2025)
The research aimed to improve the accuracy of estimating water-based paint requirements for a given wall using mathematical algorithms. The approach used in this study included a survey and document review to obtain details concerning paint. The study focused on water-based paints, including silk, weather guard, emulsion hi-cover and polyvinyl acetate (PVA) roof paint used in Tanzania’s building and construction industry. Data collected from the field study were analysed systematically. It was observed that there is a high level of familiarity in improving the accuracy of estimation of the required water-based paints, namely silk, weather guard, emulsion hi-cover and PVA roof paint for a given wall. The algorithm validation was performed by benchmarking the pre-established algorithms. Validation involved conducting five experiments: the physical study by applying two paint coats on a wall and recording the results. The percentage errors of a painting by approximating the paint using the algorithm developed gives better results than that from the different projects held in Tanzania, which was taken as a sample. The novelty of this study is based on the developed mathematical algorithm. In fact, this is among the fewer studies that mainly improve the accuracy of estimating the paint required for a given wall using a mathematical algorithm in Tanzania. There are limited studies of that nature as the majority use experience, which result in higher discrepancies.